2019
DOI: 10.13057/biodiv/d200505
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and phylogenetic analysis of Heliconia spp. collections of Purwodadi Botanic Garden (East Java, Indonesia) inferred by rbcL gene sequences

Abstract: Abstract. Hapsari L, Trimanto, Wahyudi D. 2019. Species diversity and phylogenetic analysis of Heliconia spp. collections of Purwodadi Botanic Garden (East Java, Indonesia) inferred by rbcL gene sequences. Biodiversitas 20: 1266-1283. Heliconia L. is a single genus in the family Heliconiaceae, with approximate consists of 200 species. It has wide morphological variations among and within species which led to problems in species identification. Species diversity and phylogenetic analysis using morphology and rb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…An outgroup is important in phylogenetic inference to determine the polarity or direction of evolution . Therefore, this study supports the monophyly of both families, with Strelitziaceae as the primitive relative of Heliconiaceae in accordance to some previous phylogenetic studies (Sheela et al, 2006;Marouelli et al, 2010;Iles et al, 2017;Hapsari et al, 2019). Furthermore, both methods revealed that the separation within the subgenera of Heliconiaceae was unclear and paraphyletic.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An outgroup is important in phylogenetic inference to determine the polarity or direction of evolution . Therefore, this study supports the monophyly of both families, with Strelitziaceae as the primitive relative of Heliconiaceae in accordance to some previous phylogenetic studies (Sheela et al, 2006;Marouelli et al, 2010;Iles et al, 2017;Hapsari et al, 2019). Furthermore, both methods revealed that the separation within the subgenera of Heliconiaceae was unclear and paraphyletic.…”
Section: Discussionsupporting
confidence: 92%
“…The diversity centers of Heliconia are located in tropic and subtropic regions of South America and Central America (Cronquist, 1981). However, the current distribution of Heliconia is found in many tropical countries in the world, including Brazil (Marouelli et al, 2010), Colombia (Isaza et al, 2012), Mexico (Avendaño-Arrazate et al, 2017), Indonesia (Hapsari et al, 2019). Several species of both families are used as ornamental plants for garden landscapes and cut flowers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of plastid DNA sequences in many plants revealed that the plastid genome changed only possibly a bit during evolutionary events [87,88]. In many studies, the rbcL gene has been successfully utilized in phylogenetic studies at above-species taxonomic levels [89,90]. Most studies have emphasized the importance of using rbcL in conjunction with other plant DNA barcodes [91].…”
Section: Dna Barcoding: Plastid Rbcl and Matk Loci Sequencingmentioning
confidence: 99%
“…For the topic of genetic resources, the authors made contributions to the study of more than 20 heliconia genotypes in order to determine the commercial potential as cut flower in the tropical flower industry (Loges et al, 2007;Costa et al, 2009;Rocha et al, 2010;Merida et al, 2013;Araujo et al, 2015;Loges et al, 2015;Pereira et al, 2016). Also the study of the morphology and genetic variability of this species (Hapsari et al, 2019;Kannan et al, 2019;Raizer et al, 2019) and the ability to adapt to different edaphoclimatic conditions (Tokarz et al, 2019).…”
Section: Productionmentioning
confidence: 99%